Gaze behavior and decision-making among handball referees: exploring gender and expertise differences - Świdwa, Jacek; Klatt, Stefanie; Kantanista, Adam (PeerJ, 2025)
Background Gaze behavior has been extensively studied in various sports, yet research on handball referees remains limited. Understanding gaze behavior in handball officiating is crucial for enhancing training programs, particularly for novice referees. This study investigates gaze behavior and decision-making processes among male and female handball referees of varying expertise levels. Methods A total of 51 handball referees (aged 30.25 ± 7.61 years), including 11 females and 40 males from the Polish Handball Federation, participated in the study. The sample comprised 31 higher-level referees (Super League and First League) and 20 lower-level referees (Second and Regional League). Participants wore head-mounted mobile eye-trackers to assess fixations and saccades while watching video clips of handball match scenarios. After each scene, referees made decisions based on the handball rules. Results Higher-level referees demonstrated significantly greater decision-making accuracy compared to lower-level referees (p < 0.05; Cohen’s d = 0.678), particularly in “punishment” scenarios (p < 0.001; Cohen’s d = 1.407). Although no significant differences in gaze behavior (e.g., number and duration of fixations and saccades) were observed concerning gender or expertise level, specific differences in decision-making accuracy emerged, particularly regarding expertise and free-throw scenarios. Conclusion The findings indicate that differences in decision-making accuracy among handball referees are likely influenced by factors such as experience and cognitive processing rather than gaze behavior. The absence of gender differences in gaze patterns challenges prior research suggesting systematic visual search disparities. Future studies in real-game settings are needed to explore the impact of physical and psychological demands on referees’ performance, providing practical insights for training programs.
Keywords: Eye movement; Eye-tracking; Referee; Rules of the game